Remarks on some scale worms (Polychaeta, Polynoidae) from the Southwest Atlantic with notes on the genus Eucranta Malmgren, 1866, and description of a new Harmothoe species - Barnich, Ruth; Orensanz, José; Fiege, Dieter (Marine Biodiversity, 2012)
In a collection of polychaetes from the Southwest Atlantic, off the Argentinian coast, ten scale worm species of the family Polynoidae were found. The following nine species are already known to science and their synonymy, diagnostic characters, and distribution are given together with remarks on taxonomy and geographical distribution: Eucranta mollis (McIntosh, 1876), Eucranta notialis Monro, 1936, Harmothoe exanthema (Grube, 1858), Harmothoe magellanica (McIntosh, 1885), Polyeunoa laevis McIntosh, 1885, Halosydna patagonica Kinberg, 1856, Halosydnella australis (Kinberg, 1856), Lepidasthenia esbelta Amaral and Nonato, 1982 and Showapolynoe marmorata (Hartmann-Schröder, 1965) n. comb. Additionally, a new Harmothoe species was discovered and is described in detail. Differentiating characters of the new species and Harmothoe ciliata Monro, 1936 from the Magellan region are discussed. Since two species of Eucranta Malmgren, 1866 out of four known worldwide occur in the Southwest Atlantic and since the genus has never been revised in the past, we discuss the distinguishing characters of the species and present a synoptic table. Furthermore, we raise two subspecies to species level, i.e. Eucranta villosa notialis Monro, 1936 to E. notialis Monro, 1936 and Harmothoe brevipalpa ciliata Monro, 1936 to H. ciliata Monro, 1936. Two new junior synonyms are also recognised: Harmothoe fimbriata Hartmann-Schröder, 1965 is referred to H. ciliata Monro, 1936 and Halosydna brasiliensis Kinberg, 1857 to Halosydnella australis (Kinberg, 1856). An identification key is given to all species found in the considered area.
World Polychaeta Database (WPolyD)